Islamic branding, religiosity and consumer decision on products in IAIN Salatiga - Yudha Trishananto (Indonesian Journal of Islamic Economics Research, 2019)
Islamic branding practices have recently been the main discussions within practitioners' and academicians' in the recent years. Several experts reported that Islamic branding concept has attracted interests of many companies. Muslim consumers are to be more selective in consuming their products. The labelling of halal may not always guarantee that the product is. This study aims at finding out how Islamic branding influences consumers' decision and whether consumers' religiosity correlates with Islamic branding and their decision in choosing products. The population of this research academic community of IAIN Salatiga. The samples of this research are 100 randomly chosen participants. A 5-scale Likert questionnaire was used in this study and was then analysed using double linear regression model. The results indicated that Islamic branded has the power of 9.4 % in influencing customers' decision. Meanwhile, 90.6 % of customers' decision was influenced by other factors. Additionally, religiosity as the moderating variable weakens the correlation between Islamic branding variables and customers' decision.